Ethnocentrism, Animosity, Knowledge and Country of Origin on Purchase of Jingdezhen Blue-And-White Ceramic - Yifeng, Fang; Yaacob, Husaini Bin (South Asian Journal of Social Sciences and Humanities, 2024)
This research study aims to inspect the influence of ethnocentrism, animosity, product  knowledge and the country of origin on the consumers’ purchase of Jingdezhen blue-and-white  ceramics. The study also focuses on the moderating role of country of origin and the mediating  role of product judgment. The Jingdezhen ceramics represent cultural significance and are  highly renowned, thus providing a unique context to determine the factors affecting its  purchase. The study focuses on the direct association between ethnocentrism, animosity, and  hedonic product attributes, country of origin, and purchase intention. The study focused on the  roles of familiarity and behavioral intention as moderators. Analysis for this study relies on a  quantitative approach where data is collected through a questionnaire. With the use of  convenience sampling to ensure feasibility and diversity of responses, data will be collected  from Chinese consumers. The data was analyzed through SEM, which was applied through  AMOS. The results of the study highlight that Product Judgement has insignificant impact on  Animosity and Ethnocentrism, however, it has significant impact on Country of origin, and  Product Knowledge. Consumer purchase intention of Jingdezhen blue-and-white ceramics was  found to significantly influence Animosity, Product Knowledge, and Product Judgement, and  has insignificant impact on Country of origin and Ethnocentrism. The research intends to  strengthen and add value to existing literature by providing evidence into the interplay between  the consumer purchase and cultural products.
Keywords: Ethnocentrism; Animosity; Country of Origin; Purchasing decision; China